Mathematical and Ultrasonographic Model of the Left Ventricle: in Vitro Studies - Robert OLSZEWSKI; Zbigniew TRAWIŃSKI; Janusz WÓJCIK; Andrzej NOWICKI (Archives of Acoustics, 2013)
The main objective of this study is to develop an echocardiographic model of the left ventricular and numerical modeling of the speckles- markers tracking in the ultrasound (ultrasonographic) imaging of the left ventricle. The work is aimed at the creation of controlled and mobile environment that enables to examine the relationships between left ventricular wall deformations and visualizations of these states in the form of echocardiographic imaging and relations between the dynamically changing distributions of tissue markers of studied structures.